Does past/current pain change pain experience? Comparing self-reports and pupillary responses - Yoo, Hyunkyung; Cho, Younhee; Cho, Sungkun (Frontiers in Psychology, 2023)
For decades, a substantial body of research has confirmed the subjective nature of pain. Subjectivity seems to be integrated into the concept of pain but is often confined to self-reported pain. Although it seems likely that past and current pain experiences would interact and influence subjective pain reports, the influence of these factors has not been investigated in the context of physiological pain. The current study focused on exploring the influence of past/current pain on self-reporting and pupillary responses to pain. Overall, 47 participants were divided into two groups, a 4℃–10℃ group (experiencing major pain first) and a 10℃–4℃ group (experiencing minor pain first), and performed cold pressor tasks (CPT) twice for 30 seconds each. During the two rounds of CPT, participants reported their pain intensity, and their pupillary responses were measured. Subsequently, they reappraised their pain ratings in the first CPT session. Self-reported pain showed a significant difference (4℃–10℃: p = .045; 10℃–4℃: p<.001) in the rating of cold pain stimuli in both groups, and this gap was higher in the 10℃–4℃ group than in the 4℃–10℃ group. In terms of pupillary response, the 4℃–10℃ group exhibited a significant difference in pupil diameter, whereas this was marginally significant in the 10℃–4℃ group (4℃–10℃: p<.001; 10℃–4℃: p = .062). There were no significant changes in self-reported pain after reappraisal in either group. The findings of the current study confirmed that subjective and physiological responses to pain can be altered by previous experiences of pain.